2016
DOI: 10.1186/s12879-016-1461-y
|View full text |Cite
|
Sign up to set email alerts
|

Performance of interferon-γ release assays in the diagnosis of confirmed active tuberculosis in immunocompetent children: a new systematic review and meta-analysis

Abstract: BackgroundTuberculosis (TB) is a global public health problem, causing morbidity and mortality in adults and children. The most reliable diagnostic tools currently available are the in vivo Tuberculin Skin Test (TST) and the ex vivo Interferon-γ release assays (IGRAs). Several clinical, radiological, and bacteriological features make the detection of active (overt disease) TB in children difficult. Although recently developed immunological assays such as QuantiFERON-TB Gold In-Tube (QFT-IT) and T-SPOT®.TB are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 39 publications
1
21
1
1
Order By: Relevance
“…We showed that the overall QFT-IT sensitivity in children with bacteriologically confirmed TB was significantly higher than that in adults (97.6% versus 81.0%), regardless of disease localization. Our results are in agreement with the systematic review and meta-analysis conducted by Laurenti et al, in which the QFT-IT performance in immunocompetent children with TB was 89.6% (95% CI, 79.7 to 95.7%) (26).…”
Section: Discussionsupporting
confidence: 93%
“…We showed that the overall QFT-IT sensitivity in children with bacteriologically confirmed TB was significantly higher than that in adults (97.6% versus 81.0%), regardless of disease localization. Our results are in agreement with the systematic review and meta-analysis conducted by Laurenti et al, in which the QFT-IT performance in immunocompetent children with TB was 89.6% (95% CI, 79.7 to 95.7%) (26).…”
Section: Discussionsupporting
confidence: 93%
“…Evaluation of IGRA performance in children remains limited due to small study sizes, resistance to phlebotomy, and difficulty in obtaining culture-confirmed results for reference (32). Sensitivity and specificity have been assessed in studies using either culture-confirmed cases or an exposure gradient as a surrogate for infection, but outcomes as well as proportion of indeterminate results are discordant, particularly in infants under 5 years (19,20,33,34). In our previous report, we showed good sensitivity (93.3%) and specificity (99.3%) of QFT-IT in comparison with TST for diagnosis of active TB (23).…”
Section: Discussionmentioning
confidence: 99%
“…IGRAs are not only tools for diagnosing LTBI but could be also used to integrate algorithms for active TB diagnosis. However, the routine use of IGRAs has not yet been extensively approved in children, due to concerns about their immature immune systems and discrepant results reported in different studies (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…However, there has been much debate on which screening tools to use, especially for children. [11][12][13] In 2006, the National Institute for Health and Care Excellence (NICE) in the United Kingdom (UK) issued guidelines for the screening of those exposed to TB, which, for the first time, introduced interferon-gamma release assays (IGRA), a then novel bloodbased assay, into the screening algorithm. 14 Up until that point testing for evidence of sensitisation to M. tuberculosis had been via the tuberculin skin test (TST).…”
Section: Introductionmentioning
confidence: 99%